Konsep Rahmah dalam Al-Qur’an dan Relevansinya terhadap Adversity Quotient: Studi Tafsir Tematik - Haila Fardyatullail; Shevina Putri Salsabila (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
This study examines the relationship between the concept of rahmah in the Qur’an and the concept of the Adversity Quotient as an indicator of spiritual and psychological resilience among Muslim individuals in facing life’s challenges. The significance of this research lies in its effort to integrate Islamic spiritual values with modern psychological theories in understanding human capacity to endure and manage life pressures. This study aims to explain the interpretations of Qur’anic exegetes regarding the concept of rahmah and to demonstrate its contribution to the formation of the Adversity Quotient in human character. The research employs a qualitative approach using library research and thematic analysis of relevant Qur’anic verses, combined with a descriptive-analytical method for data interpretation. The findings indicate that rahmah encompasses spiritual, psychological, and social dimensions that play a vital role in strengthening inner resilience, emotional balance, and a positive perspective toward life’s trials. The novelty of this study lies in linking rahmah as a manifestation of divine compassion with the enhancement of the Adversity Quotient within the framework of Islamic psychology. Practically, a deep understanding of rahmah can serve as a foundation for moral education, Islamic counseling, and spiritual development oriented toward resilience and human dignity.